Identifying the linguistic markers of intuition in human resource (HR) practice. (28th September 2021) - Sadler‐Smith, Eugene; Akstinaite, Vita; Akinci, Cinla
Abstract: Intuitions are judgements that arise automatically and non‐consciously. Recognising when intuitive judgements are being used and whether doing so is appropriate is an important skill both for HR practitioners and managers involved in human resource (HR) processes. Because 'intuiting' is involuntary and unconscious it is difficult to access, monitor and control, however people can access and articulate their intuitive judgements through the spoken/written word. Identifying 'linguistic markers' of intuitions in spoken/written communications could help identify when/how intuition is being used in HR and improve HR practices in areas such as selection (e.g., obviating implicit/unconscious biases) and creativity (e.g., as a source of insights). This research used computerised text analysis (CTA) to identify linguistic markers of intuition based on HR practitioners' descriptions of what happens when they 'intuit'. We outline implications of these findings for improving HR decision‐making processes and practices and their potential applications in data analytics, AI and machine learning in HR.